Phenotypic variation among silverside populations (Atherinopsidae: Atherinella brasiliensis) from distinct environments in Northeastern Brazil - Gurgel-Lourenço, Ronaldo C. (2022)
The successful adaptation of populations to a wide range of environments is a central topic in ecology. Based on the assumption that body shape may affect survival, we evaluated to what extent biotic and abiotic factors are capable of inducing morphological changes in Brazilian silverside populations (Atherinella brasiliensis). To reach this goal, we compared 18 morphological traits of specimens from five ecosystems representing three types of environment (estuary, coastal lagoon, reservoir). Populations from estuaries displayed greater anal fin area and greater caudal fin aspect ratio and area. Populations from coastal lagoons had more compressed bodies, larger heads, and slightly broader caudal peduncles. The fish from estuaries and coastal lagoons had longer caudal peduncles, larger pelvic fins and larger eye area. Population from reservoir had more depressed bodies and greater oral protrusion. Food availability explained 31% of the observed ecomorphological patterns. Overall, the morphology of the respective populations was consistent with each type of environment, making it possible to associate phenotypic variation with habitat and feeding patterns, although abiotic factors were more significant than biotic factors. In conclusion, landlocked populations of A. brasiliensis are sustainable and add to current knowledge of phenotypical variability in a species widely distributed along the Western Atlantic coast.